Plato's theory of punishment in book IX of Laws (Revista Archai, 2018)
The basis of moral responsibility is the central issue of Book IX of Laws, where Plato develops his theory of punishment, conciliating the Socratic thesis that no one is voluntarily bad (Î¿Ï…Ì“Î´ÎµÎ¹Ì€Ï‚ á¼‘Îºá½¼Î½ ÎºÎ±ÎºÎ¿ÌÏ‚), with the practical necessity for a gradation of penalties, the latter being derived from the traditional distinction between voluntary and involuntary offences. Distinguishing two independent aspects of crimes ”“ injury (Î²Î»Î¬Î²Î·) and injustice (á¼€Î´Î¹ÎºÎ¯ÌÎ±) ”“ Plato argues that the former requires only restitution, whereas injustice calls for punishment, conceived as a measure to improve the soul, affected by disordered emotions or ignorance, causes of injustice.